POSSIBILITIES OF IMPLEMENTING THE CANADIAN EXPERIENCE OF PROFESSIONAL TRAINING OF OCCUPATIONAL THERAPISTS IN UKRAINE - Deka, I. P.; Ohnystyi, A. V.; Petrytsa, P. M. (Rehabilitation and Recreation, 2023)
In the modern conditions of reconstruction and improvement of the education system of Ukraine, the process of professional training of specialists, focused on the application of foreign experience of leading countries, is of great importance. Acceleration of pace and contradiction of social changes are those macro- social factors that significantly complicate the situation not only of the individual, but also of certain social groups, which can cause them serious problems with adaptation to the conditions of a changing society. The number of people whose problems are socially determined include, in particular, internally displaced persons and soldiers returning from the Russian-Ukrainian war, as well as the elderly, persons with disabilities (adults and children). This requires a change in approaches to the professional education of many specialties, including future social workers. The purpose of the study is to develop a training module for training social workers to implement occupational therapy and test its effectiveness based on the study and generalization of Canadian experience in the field of occupational therapy and the search for possible ways of implementing this experience in Ukraine. Material and methods. Master’s degree students of the «Social Work» specialty of the Lviv Polytechnic National University, who were taught the educational module «Technologies of health preservation in social work: occupational therapy» were involved in the study. The possibilities of related disciplines and the current system of educational practices were also used for the formation of competencies in the field of occupational therapy. Forms and methods of teaching correspond to the applied nature of both occupational therapy and social work. The results. The conducted testing of students made it possible to determine that future social workers have mastered the content of the developed educational module «Technologies of health preservation in social work: occupational therapy», which has increased the level of competence of specialists and will help them better interact in a multidisciplinary team to achieve the common goal of the client. In addition, the relevance of the educational program in the specialty «Social work» to the proper preparation of the student for admission to the educational and qualification level «master» in the specialty 227 Physical therapy, occupational therapy has been determined. Conclusions. Therefore, based on the results of the evaluation of the assimilation of the content of the educational module «Technologies of health preservation in social work: occupational therapy» developed by the author, it is possible to affirm the real possibilities, needs and relationship in the study of occupational therapy by students of the «Social work» specialty. The article presents the structure and logic of the process of training social workers for professional activities in the field of occupational therapy based on the generalization of the Canadian experience in the field of occupational therapy.